2022
DOI: 10.21037/atm-22-1173
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of uterine-vaginal axis MRI-based as evaluation of surgical efficacy in women with pelvic organ prolapse

Abstract: Background: The aim of this study was to provide a potential surgical efficacy assessment in the treatment of pelvic organ prolapse (POP).Methods: A retrospective cohort study was performed on magnetic resonance imaging (MRI) imaging data of 16 non-prolapsed (control group) and 30 preoperative and postoperative POP (case group) women from 2019 to 2021 at the First Affiliated Hospital of Kunming Medical University. MRI diagnoses and measures of the relevant anatomical points at rest were used to analyze the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The study also found that “the uterus is retroverted…in patients with pelvic organ prolapse” [ 12 ]. A similar study found a statistically significant increase ( p < 0.05) in posterior rotation of the uterus in women with prolapse compared to women without prolapse [ 23 ]. These studies provide some additional support for an association of uterine prolapse with uterine retroversion but do not establish that prolapse was caused by retroversion.…”
Section: Discussionmentioning
confidence: 97%
“…The study also found that “the uterus is retroverted…in patients with pelvic organ prolapse” [ 12 ]. A similar study found a statistically significant increase ( p < 0.05) in posterior rotation of the uterus in women with prolapse compared to women without prolapse [ 23 ]. These studies provide some additional support for an association of uterine prolapse with uterine retroversion but do not establish that prolapse was caused by retroversion.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the different levels of impairment and surgical reconstruction on the biomechanical characteristics of the pelvic floor system under multifactorial impairments are not yet understood. We have conducted related studies previously: (1) POP may be associated with mechanical imbalance and loss of physiological structural features of the pelvic floor by analyzing the rules of physiological angles from MR images ( Li et al, 2022a ; Wang et al, 2022 ); (2) the occurrence of POP may also be closely associated with the impairment of the supporting structures and disruption of the biomechanical equilibrium of the pelvic floor, and the biomechanics of the normal physiological state pelvic floor in the presence of single-organ impairment are discussed ( Xie et al, 2023 ); and (3) the biomechanical mechanism of impairment and the pathogenesis of POP are investigated during the gradual evolution from the normal physiological structural state to the prolapse pathological state of the pelvic floor ( Xue et al, 2023 ). However, we have not investigated the multifactorial impairment of the pelvic floor and the biomechanical mechanisms of clinical repair and reconstruction surgery.…”
Section: Introductionmentioning
confidence: 99%